Alcoholism: a systemic proinflammatory condition - González-Reimers, Emilio; Santolaria-Fernández, Francisco; Martín-González, María Candelaria; Fernández-Rodríguez, Camino María; Quintero-Platt, Geraldine (World journal of gastroenterology : WJG, 2014)
Excessive ethanol consumption affects virtually any organ, both by indirect and direct mechanisms. Considerable research in the last two decades has widened the knowledge about the paramount importance of proinflammatory cytokines and oxidative damage in the pathogenesis of many of the systemic manifestations of alcoholism. These cytokines derive primarily from activated Kupffer cells exposed to Gram-negative intestinal bacteria, which reach the liver in supra-physiological amounts due to ethanol-mediated increased gut permeability. Reactive oxygen species (ROS) that enhance the inflammatory response are generated both by activation of Kupffer cells and by the direct metabolic effects of ethanol. The effects of this increased cytokine secretion and ROS generation lie far beyond liver damage. In addition to the classic consequences of endotoxemia associated with liver cirrhosis that were described several decades ago, important research in the last ten years has shown that cytokines may also induce damage in remote organs such as brain, bone, muscle, heart, lung, gonads, peripheral nerve, and pancreas. These effects are even seen in alcoholics without significant liver disease. Therefore, alcoholism can be viewed as an inflammatory condition, a concept which opens the possibility of using new therapeutic weapons to treat some of the complications of this devastating and frequent disease. In this review we examine some of the most outstanding consequences of the altered cytokine regulation that occurs in alcoholics in organs other than the liver.